METODE BEYOND CENTERS AND CIRCLE TIME DALAM MOTIVASI BELAJAR BAHASA ARAB DI SEKOLAH DASAR - Qisthi Khalifah; Hendi Hidayat; Agung Gumilar (Sekolah Tinggi Agama Islam (STAI) Al Hidayah Tasikmalaya, 2021)
Learning a foreign language requires sufficient motivation to support the success of the learning goals itself. One of the things that can support motivation is the use of the right method. The center method is an alternative that can be used as a support to increase student learning motivation. Learning through games, works of art that involve a lot of media and are designed in such a way in order that the knowledge to be conveyed indirectly will have a stronger impact on children's memories. The approach used in this paper is qualitative with literature studies as an effort to obtain data. In this paper, it is explained that the Beyond Centers and Circle Time method is expected to increase student learning motivation provided that the teacher applies the center method itself to its full potential.